Beyond Reflexive Measures to Examine Higher Order Pain Processing in Rats - Perry N Fuchs (Pain Research and Management)
In 1968, Melzack and Casey published a pivotal paper in which they described a model of the sensory, motivational and cognitive determinants of pain. Much of Ronald Melzack's career has been dedicated to exploring this complex relationship. Of primary importance is the influence that Ron has had on the development of some of the current research interests of the present author. For instance, Ron's theoretical approach provided the underpinnings for the development of an additional behavioural testing technique in rat models of nociception that has been recently developed in the author's laboratory. The test is based on the assumption that escape and avoidance of a stimulus are clear indications that the stimulus is aversive. It is proposed that behavioural test paradigms based on this approach provide additional information beyond the traditional measures of stimulus-evoked reflexive responses. With these tests, the underlying assumption that different aspects of pain are processed by different neural substrates can be tested.